Consuming urban living in 'villages in the city': Studentification in Guangzhou, China. (November 2015) - He, Shenjing
Against the backdrop of higher education expansion, studentification refers to a particular type of urban sociospatial restructuring resulting from university students' concentration in certain residential areas. Over the last decade, studentification has evolved into different forms and has spread to different locales. This study aims to provide a contextualised understanding of this distinct phenomenon in China so as to decode the complex dynamics of urban sociospatial transformation in the Chinese city. In this paper, I present a line of empirical evidence based on fieldwork in Xiadu Village and Nanting Village, two studentified villages close to university campuses in Guangzhou. These two villages exemplify different consumption and spatial outcomes of studentifcation, owing to different institutional arrangements, types of studentifiers and roles of villagers. Yet, in both villages, studentification has profoundly transformed the economic, physical, social and cultural landscapes. Notably, rather than the spatialisation of compromised and marginalised residential choices by higher education students, studentification in China is better interpreted as the spatial result of students' conscious residential, entrepreneurial and consumption choices to escape from the rigid control of university dorms, to accumulate cultural and economic capital, as well as to actualise their cultural identity. In the Chinese context, studentification provides a useful prism to understand a unique trajectory of urbanisation: re-urbanising the 'villages in the city' through bringing in urban living/urban consumptions. In the long run, studentification could provide a potential solution to sustain and upgrade the villages in the city.